HUKUM ADAT DALAM PEMBAHARUAN DAN PEMBANGUNAN HUKUM NASIONAL - Ervina Dwi Indriati; Indira Hastuti (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
Efforts to form a national legal order that serves national interests (as directed by the GBHN), of course, must pay attention to existing laws (customary law / laws that applyin society and colonial law) as well as laws that are currently developing in the international world. This paper will discuss legal development in Indonesia in terms of a systems approach with customary law as one of the inputs. The process of development (formation) of national law by itself will be influenced by the state of the cultural subsystem, political subsystem and economic subsystem that currently exists and applies in Indonesia. In the context of customary law as input in order to achieve the goal of becoming National Law, its position as input itself has also been influenced by these subsystems.